WAYS TO DEVELOP ORAL SPEECH IN A FOREIGN LANGUAGE (Scientific journal of the Fergana State University, 2024)
This article talks about the ways to develop oral speech competence in foreign language classes, the ability to give oral information in a foreign language, to be able to talk, and to acquire the skills of listening and understanding speech in a foreign language related to the studied topic. In the article, the factors affecting oral speech in a foreign language, especially motivation, interest in language, educational strategies, language ability, intelligence, etc., are directly related to each other, based on examples. American scientist Robert Gardner states that motivation is one of the influencing factors in teaching speaking in a foreign language, and motivation has a strong influence on the mind of the language learner. The article also notes that practicing speaking outside of class, attending courses, and using social networking opportunities are of particular importance to students studying German as a specialty. It was emphasized that students should learn the language consciously, which method is suitable for them, and the factors that lead to or hinder the development of their oral speech. The article also emphasizes the methods and technologies developed by the German scientist B. Taubenbock for the development of oral speech in classes.